Into the Digital Wild: Utilizing Twitter, Instagram, YouTube, and Facebook for Effective Science and Environmental Communication - Pavelle, Sophie; Wilkinson, Clare (Frontiers in Communication, 2020)
Recent years have seen an upsurge in the digital environment and the reliance placed upon it by society. This case study reports on a project which sought to examine how the digital environment can be utilized for science communication, exploring the role of social media and particularly short online videos, as an effective means through which to engage the public with science, environment and conservation messages. Using as its focus a 300-mile trek around the coast of Cornwall (Sophie’s Wild Cornwall) we examine how science was communicated real-time using online videos and social media over a five-week period, as well as data from an online public opinion survey (n=129). The observations gleaned identify a number of key themes for others wishing to adopt digital approaches within their science communication activities, including the role of web-based presenter-led narratives, the value of accessibility and interaction on social media platforms, and online videos potential for stimulating proactive, participatory engagement and interest in an environmental context. Effective online video use requires a balance between crafting an informative yet entertaining narrative without compromising scientific accuracy; yet ultimately, social media platforms may represent a potential ‘stepping-stone’ for practitioners to consider implementing in a journey towards ‘upstream engagement’.